The Kurdistan Region of Iraq’s Accession to the World Trade Organization - The Possibility and Legal Challenges - (A Comparative Analytical Study) - Saleh, Rebaz Khurshid Muhammad (Journal of Legal and Political Studies, 2014)
WTO allows the accession of separate customs territory, and the examples are Taiwan and HKSAR. The conditions for such accession are for the territory to apply a different tariff and to have freedom in its trade and trdae-related aspects. In this research we evaluated the possibility of accession of KRG to WTO through comparing Taiwan and HKSAR with KRG, and we found that KRG have the general requirements, with some obstacles in Iraqi constitution namely the exclusive authorities of the federal government which could be overcomed through narrow interpretation of the constitution, and other international obstacles such as the accession of a territory before the state itself, and the issue of diplomatic representation of a territoty in WTO.
Keywords: WTO; Territory; international obstacles; KRG